Between‐ and within‐population drivers of haemosporidian prevalence and diversity in American robins Turdus migratorius - Alex E. Jahn; Daniela de Angeli Dutra; Jeffrey A. Bell; Janice H. Dispoto; Alan Fecchio; Ellen D. Ketterson; Kamila M. D. Kuabara; Tara M. Smiley; Taylor B. Verrett; Jason D. Weckstein; Emily J. Williams; Daniel J. Becker (Journal of Avian Biology)
Avian haemosporidians are a diverse group of parasites that infect birds worldwide and have been a major focus of research for decades. Yet, few studies have identified the drivers of infection at the intraspecific host level. We aimed to study the drivers of prevalence and diversity of haemosporidian parasites infecting a common North American songbird species, the American robin Turdus migratorius, which breeds across most of the continent. We found little seasonal variation in haemosporidian prevalence in robins, although we detected a significantly positive relationship between robin breeding latitude and co‐infection with different haemosporidian parasite lineages. Additionally, robins infected with Plasmodium had substantially better body condition than uninfected robins, which could be due to migratory culling. We detected 31 haemosporidian lineages among the robins we sampled, of which eight were novel. When matched against known haemosporidian lineages, our results suggest that robins harbor a higher diversity of haemosporidian parasites than previously known. The results of this study suggest that comparisons of common, widespread bird species such as robins across their range could help unveil novel aspects of the haemosporidian–host relationship and how such a relationship may change under current and future rapid environmental change.